Rainwater Quality Improvement Model as an Alternative Source for Drinking Water in Mojoagung District, Jombang Regency - Galih M Fatian; Hari Siswoyo; Riyanto Haribowo (Civil and Environmental Science Journal (CIVENSE), 2022)
Water is a basic need for humans, yet often the quality and quantity become cronstrained as happened in Mojoagung District, Jombang Regency. During the dry season, the potential for water reserves available for use is rainwater that has been stored. Based on laboratory tests, the quality of the stored rainwater is below the quality standard due to its high KMnO4 (Calium Permanganate) content. Hence we need a simple filter to improve the water quality. Researchers have conducted experiments with the filter composition of zeolite, activated charcoal, activated sand, sterile cotton, and aquarium filter. The results of the filtration process showed a significant decrease in potassium permanganate. The filtration results from the filter with the composition of zeolite, activated charcoal, activated sand, sterile cotton, and an aquarium filter sequentially 5 cm, 10 cm, 15 cm, 4 cm, and 2 cm succeeded in reducing potassium permanganate levels from 11.73 to an average of 2.12 mg. /l. The best filter due to experimental activities will be integrated with rainwater harvesting structure system which has been discussed along with related social community and stakeholders.